CEO NARCISSISM AND FIRM VALUE: THE ROLE OF ENVIRONMENT SOCIAL GOVERNANCE DISCLOSURE AS MEDIATOR - Bonita Prabasari; Adhi Pradiptya; Rahma Prafinta Sari (Kajian Akuntansi, 2026)
CEOs exhibiting narcissistic traits are frequently associated with aggressive strategic behaviors, including business expansion, innovation, and excessive self-promotion. Prior studies suggest that CEO narcissism can use ESG disclosure as a mechanism for image building (window dressing) to enhance corporate reputation, while transparent ESG practices have the potential to increase investor confidence. Accordingly, this study aims to examine whether ESG disclosure mediates the relationship between CEO narcissism and firm value. The study comprises firms listed in the LQ45 index of the Indonesia Stock Exchange during 2019–2024 and employs multiple linear regression and the Sobel test using IBM SPSS Statistics version 25. The results reveal that CEO narcissism and ESG disclosure significantly affect firm value. However, CEO narcissism does not affect ESG disclosure, and ESG disclosure does not mediate the relationship between CEO narcissism and firm value.